Chitosan-mediated synthesis of flowery-CuO, and its antibacterial and catalytic properties. (15th September 2017) - Raghavendra, Gownolla Malegowd; Jung, Jeyoung; Kim, Dowan; Seo, Jongchul
Highlights: In situ synthesis of CuO in a chitosan solution. CuO shows flower-like morphology. CuO exhibits good antibacterial and catalytic properties. Abstract: In the current investigation, CuO with a flower-like morphology has been successfully synthesized in situ in a chitosan medium (0.0015 g mL −1 ) from copper nitrate (Cu(NO3 )2 ·3H2 O) and ammonia solution via a facile microwave-induced method. The as-prepared CuO was characterized by SEM, TEM, EDX, XRD, FTIR and TGA. The antibacterial activity of the flower-CuO against Escherichia coli was examined by analyzing colony forming units, and it was proved that the flower-CuO was able to kill >99% bacteria. Further, the flower-CuO exhibited excellent catalytic activity towards the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 . The reaction kinetics followed a pseudo-first-order rate law with a rate constant of 0.183 min −1 . To the best of our knowledge, this is the first time that copper oxide with the flower-like morphology has been synthesized by using a chitosan solution.